2005
DOI: 10.1523/jneurosci.4249-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Triple Knock-Out ofCNTF,LIF, andCT-1Defines Cooperative and Distinct Roles of these Neurotrophic Factors for Motoneuron Maintenance and Function

Abstract: Members of the ciliary neurotrophic factor (CNTF)-leukemia inhibitory factor (LIF) gene family play an essential role for survival of developing and postnatal motoneurons. When subunits of the shared receptor complex are inactivated by homologous recombination, the mice die at approximately birth and exhibit reduced numbers of motoneurons in the spinal cord and brainstem nuclei. However, mice in which cntf, lif, or cardiotrophin-1 (ct-1) are inactivated can survive and show less motoneuron cell loss. This sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 55 publications
(77 reference statements)
4
46
0
Order By: Relevance
“…Because no information exists about the involvement of the NF-B pathway mediating MN survival, we decided to analyze this subject in our MN model. Spinal cord MNs respond to a variety of NTFs; requirements for these factors vary depending on the MN subpopulations and the developmental period (Holtmann et al, 2005). Our previous work (our unpublished results and Gou-Fabregas et al, 2009) and that of others (Arce et al, 1999) showed that using a cocktail of NTFs enhanced MN survival compared to the survival rate obtained by each NTF separately.…”
Section: Neurotrophic Factor Stimulation Induces Nf-b Pathway Activatmentioning
confidence: 49%
See 1 more Smart Citation
“…Because no information exists about the involvement of the NF-B pathway mediating MN survival, we decided to analyze this subject in our MN model. Spinal cord MNs respond to a variety of NTFs; requirements for these factors vary depending on the MN subpopulations and the developmental period (Holtmann et al, 2005). Our previous work (our unpublished results and Gou-Fabregas et al, 2009) and that of others (Arce et al, 1999) showed that using a cocktail of NTFs enhanced MN survival compared to the survival rate obtained by each NTF separately.…”
Section: Neurotrophic Factor Stimulation Induces Nf-b Pathway Activatmentioning
confidence: 49%
“…In the present work, we investigated whether NF-B signaling mediates the survival effect induced by NTFs on the spinal cord motoneurons (MNs). The large variety of neurotrophic molecules that can support MN survival in vivo and in vitro indicates that developing and postnatal MNs depend on a cooperation of these molecules that is so far not fully understood (Oppenheim, 1996;Holtmann et al, 2005). NTFs promoting MN survival in vivo and in vitro belong to different gene families and activate several signaling pathways (Soler et al, 1999;Dolcet et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, in CNTF KO mice, there is similarly no increased loss of motor neurons during the first weeks of life (24,25). This, perhaps, is not surprising, given that levels of CNTF are low during development and, although Schwann cells are the richest source of CNTF in the adult peripheral nervous system, levels only rise during the first postnatal week (26)(27)(28). Knockout of the CNTF gene did result in motor neuron loss 28 weeks after birth (24); however, RegIII␤ mice did not show motor neuron loss in later adult stages.…”
Section: Discussionmentioning
confidence: 95%
“…The gp130 cytokine family is characterized by functional redundancy, and the phenotypes of mice lacking individual cytokines [12,17,28,29,45] are much less severe than the phenotypes of mice lacking their shared receptors [10,30,46]. Nonetheless, the early and robust expression of CT-1 in the developing heart tube, and the sustained expression of CT-1 in the adult heart, suggested that CT-1 played a unique role in promoting cardiac myocyte survival and hypertrophy during development and after injury.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of CT-1 results in the loss of a subset of motoneurons [12,17], and in a decreased number of preganglionic sympathetic neurons [18]. Other related cytokines are involved in supporting motoneuron survival and function [17], but CT-1 appears to be the only cytokine required for the survival and maintenance of preganglionic sympathetic neurons [18]. Postganglionic sympathetic neurons projecting to the heart increase heart rate, ventricular pressure, and contractility through activation of cardiac beta receptors.…”
Section: Introductionmentioning
confidence: 99%